Nimotuzumab combined with chemoradiotherapy for the treatment of cervical cancer: A meta-analysis of randomized controlled trials - Yuan, Yan; Chen, Jiuzhou; Fang, Miao; Guo, Yaru; Sun, Xueqing; Yu, Dehong; Guo, Yilong; Xin, Yong (Frontiers in Oncology, 2022)
Objectives: To assess the clinical efficacy and toxicity of nimotuzumab in combination with chemoradiotherapy or chemoradiotherapy alone in the treatment of cervical cancer. Methods: Literature from PubMed, Embase, Cochrane Library, Web of Science, China National Knowledge Infrastructure, China Biomedical Medcine, Wanfang database, and VIP database were systematically searched. Ultimately, a total of six randomized controlled trials (n=393) were included in our study for meta-analysis. Results: 393 patients, of which 197 were in the nimotuzumab combined with chemoradiotherapy group and 196 in the chemoradiotherapy group were eventually included. The results of our meta-analysis showed complete remission rate (risk ratio [RR] =1.34, 95% confidence interval [CI] :1.08-1.65, P=0.007), object response rate (RR=1.30, 95% CI:1.16-1.44, P<0.05), 3-year survival rate (RR=1.27, 95% CI:1.06-1.51, P=0.008) in the nimotuzumab combined with chemoradiotherapy group were significantly improved compared with the chemoradiotherapy group. The difference was not statistically significant when comparing the incidence of adverse reactions (such as leukocytopenia, gastrointestinal reaction, radiocystitis, and radioproctitis) between the two groups. Conclusions: Nimotuzumab in combination with chemoradiotherapy has some advantages over chemoradiotherapy alone for the treatment of cervical cancer and does not increase toxicities. Therefore, nimotuzumab has the potential to be an effective treatment for cervical cancer, but further evidence from large scale randomized controlled trials is needed.